Synthesis of two-dimensional ZnO nanopellets by pyrolysis of zinc oleate - Chiu, W.S. (2008)
We report the non-hydrolytic solution phase synthesis of two-dimensional zinc oxide (ZnO) nanopellets by using self-made organometallic compound (zinc (II) oleate, Zn(C18H33O2)2) as single precursor. Zn(C18H33O2)2 is prepared by ion exchange reaction between non-toxic fatty acid (palm oil extract) and ion Zn2+. The controlling process of thermal pyrolysis of precursor is carried out under inert argon (Ar) atmosphere. This technique is very effective and reproducible in controlling the shape of ZnO semiconductor nanostructures. The as-synthesized ZnO nanocrystals are found in two-dimensionally well-faceted triangular and hexagonal thin pellet structures. Transmission electron micrograph(s) (TEM) show that the morphologies of ZnO nanopellets can be controlled by annealing duration. X-ray powder diffraction patterns reveal that all the peaks of ZnO nanopellets can be well indexed with standard hexagonal phase of ZnO crystal structure. Â© 2008 Elsevier B.V. All rights reserved.